2006
DOI: 10.1042/bj20051121
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal alkaline sphingomyelinase hydrolyses and inactivates platelet-activating factor by a phospholipase C activity

Abstract: Alkaline sphingomyelinase (alk-SMase) is a new member of the NPP (nucleotide pyrophosphatase/phosphodiesterase) family that hydrolyses SM (sphingomyelin) to generate ceramide in the intestinal tract. The enzyme may protect the intestinal mucosa from inflammation and tumorigenesis. PAF (platelet-activating factor) is a pro-inflammatory phospholipid involved in pathogenesis of inflammatory bowel diseases. We examined whether alk-SMase can hydrolyse and inactivate PAF. [ 3 H]Octadecyl-labelled PAF was incubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 45 publications
0
57
0
Order By: Relevance
“…Because the WPG loop is present in all other E-NPPs, a different mode for lysophosphatidyl and sphingosyl binding must exist in NPP6 and NPP7. Compared to the lysophospholipase D activity of NPP2, these enzymes exhibit lysophospholipase C activity [388,391]. In addition, NPP6 shows high specificity for choline head groups.…”
Section: Phylogenetic Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the WPG loop is present in all other E-NPPs, a different mode for lysophosphatidyl and sphingosyl binding must exist in NPP6 and NPP7. Compared to the lysophospholipase D activity of NPP2, these enzymes exhibit lysophospholipase C activity [388,391]. In addition, NPP6 shows high specificity for choline head groups.…”
Section: Phylogenetic Relationshipmentioning
confidence: 99%
“…Interestingly, its catalytic activity is inhibited by ATP but not by ADP or AMP. In addition, NPP7 was found to cleave the phosphocholine head group and thus to inactivate platelet-activating factor, a pro-inflammatory phospholipid involved in the pathogenesis of inflammatory bowel disease [391].…”
Section: General Properties and Functional Rolementioning
confidence: 99%
“…Cloning studies reveal that alk-SMase shares no structural similarities with other SMases, but belongs to the nucleotide pyrophosphatase phosphodiesterase (NPP) family and is now also called NPP7 (11,13,14). However, NPP7 is inactive toward nucleotide phosphate esters but has specific activities against phospholipids containing a phosphocholine moiety, including sphingomyelin, platelet-activating factor (PAF), and lysophosphatidylcholine (13,15). Hydrolyses of these substrates result in the increased ceramide formation, inhibited proinflammatory effects of PAF, and reduced formation of lysophosphatidic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Second, it hydrolyses and inactivates platelet-activating factor, a potent proinflammatory and proliferative molecule in the intestinal tract . Finally, it degrades lysophosphatidylcholine by a phospholipase C activity, thus reducing the formation of lysophosphatidic acid, a potent factor that stimulates cell migration and angiogenesis (Duan, 2006;Wu et al, 2006). We previously found that alk-SMase activity was decreased in colonic adenomas and carcinomas, in familial adenomatous polyposis and in longstanding ulcerative colitis (Hertervig et al, 1997(Hertervig et al, , 1999Sjöqvist et al, 2002).…”
mentioning
confidence: 99%